Analisis Neraca Air dalam Ketersediaan Air Terhadap Perubahan Iklim di Beberapa Sub DAS Musi - Puspitahati Puspitahati; Edward Saleh (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2017)
Puspitahati et al, 2017. Analysis of Water Balance in Water Supply Against Climate Change in some Sub-Watersheds Musi. JLSO 6(2):192-202.Â Rainfall and land cover in the Musi Sub-watershed affect water availability. Both of these components are inputs from the water balance which will affect fluctuations and water level so that it will affect evapotranspiration, run off, and flowrate. The purpose of the study was to determine how the effects of climate change on water availability in the Sub-watershed of Musi Watershed. This study was focus on four Sub-watersheds contained on the Musi river basin, namely Musi Sub-watershed, Komering Sub-watershed, Ogan Sub-watershed and Lematang Sub-watershed. This research was conducted at the Laboratory of Soil and Water Engineering, Department of Agriculture Technology, Faculty of Agriculture, Sriwijaya University from September 2013 to January 2014. Methods used in this research were descriptive method, the study of literature and secondary data taking, while the analysis was done with tabulation and graphs. The conclusion were 1) The availability of water was affected by changes in rainfall, population growth, and land cover types, 2) The highest rainfall was in Komering Sub-watershed equal to 105.23 mm/month, the highest run off was in Komering Sub-watershed equal to 33.67 mm/month, while the highest of evapotranspiration was inÂ  Lematang Sub-watershed equal to 121.69 mm/month. Thus, we can find out how the effects of climate change on water availability in sub-watersheds in the Musi River Basin.